Incorporating autonomicity and trustworthiness aspects for assessing software quality - Dehraj, Pooja; Sharma, Arun; S. Grover, P (International Journal of Engineering and Technology, 2017)
Autonomic computing covers few self-abilities like self-configuration, self-healing, self-optimization, self-protection, self-adaptability, self-awareness, self-openness etc. in software systems. These self-abilities will lead towards lowering the overall maintenance cost of the software because of minimum level of human intervention. The term Autonomicity refers to the level of autonomic (self) features implemented in the system. The International software quality standard ISO 9126 is now replaced by new software product quality standard ISO/IEC 25010:2011 which defines the framework/model to specify and evaluate the quality of software as a product. However, this does not take into account the self-* features (autonomic aspects) and trust factor of modern day software systems. The present paper proposes here that autonomic characteristics of any system must be considered while assessing the quality of any software product. This autonomic-oriented quality model may be used to assess the software quality in a number of domains. Therefore, a new enhanced software quality model is proposed which considers autonomicity and trustworthiness as a factor of quality.